"Todo vagabundo é maconheiro, mas nem todo maconheiro é vagabundo": um estudo com consumidores estáveis de maconha - Lima Filho, Francisco de Assis (2010)
Marijuana is the most consumed psychoactive substance in the world. The scientific literature about Marijuana focuses mainly It´s pharmacological effects, actions of prevention, public policies for drug users and abusive consumers. Only a small number of studies were dedicated to investigate the psycho-social aspects of the consumption, just as values and practice of social integrated marijuana consumers. From this gap, we intent to investigate the marijuana consumption of social integrated people, as well as their social representations of marijuana. For that we developed a qualitative study with 10 male marijuana stable consumers between 20 and 32 years old. To collect the data we used interview based on semi-structured script and the data analysis were made using a method based on phenomenology together with content analysis. The main results demonstrate: an individuals identification to consumption norm non-associated to abusive practices, justified by their fulfillment of social duties and the observance of social controls; the identification and approximation of these drug consumers to the social reality of non-consumers; the importance of the re-signification, by part of these individuals, of information about marijuana initially provided by part of the social institutions (family, school, religion) for their consumption regularity settlement; the marijuana"s consumption standard and It"s perception by the consumers are not based only on medical paradigm, legal – other non-quantified logic are use on the selfclassification and regard subjective aspects, consumpstion situations, activities that will be developed, availability to consume, etc; the social representations of marijuana existent in these individuals speeches demonstrate It"s effects demystification, It"s link to pleasure and It"s natural nature. We conclude that the investigation of knowledge or perception of marijuana consumers about their own consumption practice allow us to understand this phenomenon in a less fragmented way.